2012
DOI: 10.1159/000335178
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Distinguish Granule-Stored from de novo Synthesized Tumor Necrosis Factor Secretion in Human Mast Cells

Abstract: Background: Mast cells are immune cells derived from hematopoietic precursors that mature in the tissue microenvironment. Mast cells are critical for allergic, immune and inflammatory processes, many of which involve tumor necrosis factor (TNF). These cells uniquely store TNF in their secretory granules. Upon stimulation, mast cells rapidly (30 min) secrete β-hexosaminidase and granule-stored TNF through degranulation, but also increase TNF mRNA and release de novo synthesized TNF 24 h later. The regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 84 publications
0
21
0
2
Order By: Relevance
“…Moreover, IL-33 has been implicated in the pathogenesis of psoriasis via keratinocyte and mast cell activation (30), and has been reported to be elevated in the serum of patients with generalized psoriasis and correlated with high serum TNF levels (31). In addition to the newly synthesized TNF secretion reported here, mast cells are the only immune cells that also store and rapidly secrete preformed TNF (32)(33)(34)(35)(36). Given the foregoing findings, we decided to investigate whether the interactions between SP and IL-33 affect human mast cell secretion of TNF.…”
mentioning
confidence: 71%
“…Moreover, IL-33 has been implicated in the pathogenesis of psoriasis via keratinocyte and mast cell activation (30), and has been reported to be elevated in the serum of patients with generalized psoriasis and correlated with high serum TNF levels (31). In addition to the newly synthesized TNF secretion reported here, mast cells are the only immune cells that also store and rapidly secrete preformed TNF (32)(33)(34)(35)(36). Given the foregoing findings, we decided to investigate whether the interactions between SP and IL-33 affect human mast cell secretion of TNF.…”
mentioning
confidence: 71%
“…This phenomenon may be due to the distinct regulatory mechanisms for TNF-a synthesis and secretion [35]. Actually, there are multiple pathways responsible for the release of newly synthesized or stored cytokines [36]. For example, the granule-stored TNF is rapidly (30 min) secreted from human mast cells (a bone marrow-derived immune cell) upon stimulation, which differs from the delayed (12e24 h) release of newly synthesized TNF [36].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there are multiple pathways responsible for the release of newly synthesized or stored cytokines [36]. For example, the granule-stored TNF is rapidly (30 min) secreted from human mast cells (a bone marrow-derived immune cell) upon stimulation, which differs from the delayed (12e24 h) release of newly synthesized TNF [36]. Notably, regarding the stimulation intensity and duration, rgcHSP70 displayed more potential to regulate the secretion rather than the transcription of the cytokines, promoting us to speculate that gcHSP70 may induce release of proinflammatory cytokines in a rapid or efficient kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Apoptotic cells could in turn release high amounts of pro-inflammatory IL-1 and TNF, further enhancing skin inflammation. We previously showed that both preformed and newly synthesized TNF can be released from mast cells, 7 the numbers of which seem to be increased in the centre of vitiligo lesions. 2 A recent paper reported that chemically induced vitiligo led to increased production of IL-6 and IL-8.…”
Section: Reportmentioning
confidence: 99%